MANAJEMEN NON-OPERATIF ABSES SEREBELLUM - Putri Irsalina; Paulus Sugianto (NEURONA, 2021)
A brain abscess is a severe infection that needs to be treated early. The increased mortality for brain abscesses is caused by modern diagnostic imaging and antibiotics that can penetrate into the central nervous system and abscesses. A cerebellar abscess was reported, with the chief complaint of chronic progressive headache. Head contrast magnetic resonance imaging (MRI) results show the presence of a right cerebellar abscess with a source of infection with otitis media and mastoiditis. Prover antibiotics and contrast head MRI evaluation show resolution of abscess diameter. Keywords: Cerebral abscess, cerebellar abscess, otitis media